PERAMALAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) PROVINSI BALI DENGAN MENGGUNAKAN METODE FUZZY TIME SERIES - ARYA WANAYASA, I GUSTI NGURAH; NILA KENCANA, I PUTU EKA; NILAKUSMAWATI, DESAK PUTU EKA (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012, 2012)
The purpose of this research is forecasting the growth of the GDRP in Bali Province on 2011. The fuzzy time series method and Holt-Winter’s exponential smoothing method used to forecast the GDRP in Bali Province on 2011 by using the data of Bali Province’s GDRP constant prices of year 2000 from first quarter of 1991 until fourth quarter of 2010. Then, the forecasting result of both method s compared by see the AFER and MSE value on each method. The comparison result shows the forecasting method by using Holt-Winter’s exponential smoothing is 7.13% while using the fuzzy time series method is 0.64%, these shows the forecasting using fuzzy time series method have a higher accuracy rate compared to Holt-Winter’s exponential smoothing method with the difference of forecasting error rateis6.49%.
Keywords: GDRP forecasting; fuzzy time series; Holt-Winter’s exponential smoothing